2015
DOI: 10.1002/ird.1903
|View full text |Cite
|
Sign up to set email alerts
|

The Values of Crop Coefficients and Bowen Ratio of Field Crops in Areas with Insufficient Precipitation in Central Europe

Abstract: The aim of this study, based on measurements of actual evapotranspiration of vegetation, was to determine the values of the crop coefficient (K c ) for selected crops and the effect of growth on the dissipation of radiation energy. The actual evapotranspiration (ET a , mm day

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…The main advantage of this method is that the assessment of ET 0 is based on meteorological data from reference stations, while k c values account for specific crop types and growing conditions. For several tropical fruits and crop species, such as apple (Marsal et al, 2013), kiwi fruit (Silva et al, 2008), Sorghum bicolor (Zábranský et al, 2015), maize (Zhang et al, 2013) and wheat (Yan et al, 2020; Zheng et al, 2020), k c values different from the FAO tabular values have been reported (Allen et al, 1998). However, studies on the crop coefficient of tea trees are rare for some special areas, even though the FAO has given a reference value of k c for tea trees.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of this method is that the assessment of ET 0 is based on meteorological data from reference stations, while k c values account for specific crop types and growing conditions. For several tropical fruits and crop species, such as apple (Marsal et al, 2013), kiwi fruit (Silva et al, 2008), Sorghum bicolor (Zábranský et al, 2015), maize (Zhang et al, 2013) and wheat (Yan et al, 2020; Zheng et al, 2020), k c values different from the FAO tabular values have been reported (Allen et al, 1998). However, studies on the crop coefficient of tea trees are rare for some special areas, even though the FAO has given a reference value of k c for tea trees.…”
Section: Introductionmentioning
confidence: 99%